Nilai Nutrisi dan Rendemen Ekstrak Metanol Pelet Katuk Depolarisasi sebagai Parameter Standar Mutu Produksi - Agik Suprayogi; Fadjar Satrija; Muladno Muladno; Ronald Tarigan; Afton Atabany; Novriyandi Hanif; Welly Sugiono; Yuliantoni Yuliantoni (Institut Pertanian Bogor, 2023)
Standardization of the quality of the depolarized katuk pellet production process as a feed additive is very important to maintain product quality. The production process requires dry katuk leaves (DKK) as raw materials which are then processed into depolarized katuk leaves (DKD), and continues in the pelleting process to become depolarized katuk pellets (PKD). Quality standard can be done by measuring the parameters of nutritional value and also the yield of methanol extract. Nutritional values were obtained from the results of proximate analysis, namely the percentage of dry matter, ash content, crude protein, crude fiber, crude fat, beta-N, calcium, phosphorus, and gross energy (Cal/g). Mean while, the yield of methanol extract was obtained by maceration using methanol solvent. This study aims to evaluate the nutritional value and yield of crude methanol extract of katuk leaves (DKK, DKD, PKD) which can be used as a quality assurance standard for the depolarized katuk pellet production process. In general, the nutritional value of DKD and PKD had the same value as that of DKK, except for calcium which was quite high (P<0.05) in DKD and PKD, and the percentage of crude fiber was lower (P<0.05) in PKD compared to DKK and DKD. The percentage of crude fat in pellets (PKD) was higher (P<0.05) when compared to DKK and DKD. The yield of methanol extract was very high (P<0.05) in DKK, compared to DKD and PKD. The nutritional parameters and the yield of the katuk leaf extract can be used as quality assurance standards for the depolarized katuk pellet production process. Keywords: depolarization, katuk, methanol, nutrition, pellet